Effect of the BaO-Na2O-Nb2O5-P2O5 glass addition on microstructure and dielectric properties of BNN ceramics. (2022) - Ihyadn, A.; Mezzane, D.; Amjoud, M.; Lahmar, A.; Bih, L.; Alimoussa, A.; Luk'yanchuk, I.A.; El Marssi, M.
Abstract: Barium sodium niobate Ba2 NaNb5 O15 (BNN) ceramics with different amounts of BaO-Na2 O-Nb2 O5 -P2 O5 (BNNP) glass were prepared via the conventional solid-state method. The effect of glass content on structural, microstructure and dielectric properties of BNN ceramics was investigated. The XRD results showed that no secondary phase was formed after adding BNNP glass. It was found that such additions reduce the average grains size and refine the microstructure of the obtained ceramics. Moreover, the samples exhibited a stable dielectric constant over the temperature range of 25°C–150°C and their dielectric constants were significantly improved. The ceramic with 7.5 wt% BNNP glass content showed a dielectric constant which is more than twice as much as that of pure BNN ceramic, as well as a low dielectric loss less than 5%.